Functional Form in Regression Models of Tobin's q - Hirsch, Barry T.; Seaks, Terry G. (The Review of Economics and Statistics, 1993)
The Box-Cox transformation is used to compare alternative functional forms of market value equations. Based on evidence from a panel of 480 publicly-traded U.S. manufacturing companies and two additional data sets used previously in the literature, the semilog form of a Tobin’s q equation is found to be strongly preferred to the commonly estimated linear form. We provide illustrations in which inferences can be affected by the choice of functional form. The authors thank Zvi Griliches, Hendrik Houthakker, and two anonymous referees for helpful discussion and suggestions, and Jerry Stevens for providing access to one of the data sets examined in Section III. Remaining errors are ours. A longer working paper version is available on request. 1